On rational behavior in multi-attribute riskless choice - (:unkn) unknown (ELSEVIER, 2021)
We theoretically compare and contrast two commonly used types of choice strategies in a riskless, multi-attribute setting: (1) the win-win (or Pareto improving) strategy, and (2) the tradeoff strategy. Both strategies can be used and are used in Multiple Criteria Decision Making theory and practice. In the win-win strategy, consumers (or decision-makers) consider, which goods they want to add to their basket. In the tradeoff strategy consumers make pairwise choices between different (efficient) baskets, where they have to give up in some goods to gain in other goods. We postulate a choice model based on standard assumptions in economics/behavioral decision theory. The key underlying theoretical assumptions in our choice model are increasing and concave single dimensional value functions with decreasing marginal values (win-win setting) and the Tversky-Kahneman reference-dependent model of choice with loss aversion (tradeoff setting). The multi-attribute value function is assumed additive and separable. We study the decision-maker's consistency with our theory in both strategies. The perspective is that of an outside observer (an analyst). The basket is filled either with different or identical goods. We compare and contrast the win-win and tradeoff strategies and draw conclusions for the development of our field. We use an empirical experiment to motivate our considerations. (c) 2020 Elsevier B.V. All rights reserved.
Keywords: Choice behavior; Multiple criteria decision making; Riskless choice; Win-win; Tradeoff; Loss aversion; Decreasing marginal values; CRITERIA DECISION-MAKING; LOSS AVERSION; MULTIPLE; OPTIMIZATION